Structural, Electronic & Magnetic Properties of Pristine and Defected ZnO Monolayer: First-Principles Study - Neupane, H. K.; Rijal, A.; Adhikari, N. P. (Journal of Nepal Physical Society, 2023)
Electronic and magnetic properties of materials are appealing properties and have budding applications in the devices. In this work, we have investigated the structural, electronic and magnetic properties of pristine Zinc-Oxide (ZnO) and Oxygen-defected Zinc-Oxide (ZnO_O) materials by spin-polarized density functional theory (DFT) method. Structural properties are studied by calculating their total ground state energy, and found that both are stable 2D materials. It is also found that ZnO have higher stability than of ZnO_O material. Electronic properties of considered materials are examined by analyzing of their band structure, density of states (DOS) calculations and found that ZnO is a direct band gap, n-type semiconductor material in its pristine form and an indirect band gap, p-type semiconductor material in its Oxygen-defected form (ZnO_O). Magnetic properties of pristine and defected ZnO are investigated by analyzing their density of states (DOS) and partial density of states (PDOS) calculations, they revealed that ZnO and ZnO_O have non-magnetic properties.